Navigating Ethical and Legal Challenges in Artificial Nutrition and Hydration: The Role of Guidelines and Patient Autonomy - Karaboue, Michele Ahmed Antonio; Dimauro, Elisabetta (Progress in Nutrition, 2025)
This article examines the complex ethical, medical, and legal issues surrounding the use of Artificial Nutrition and Hydration in critically ill patients. It highlights the importance of guidelines in clinical decision-making, while also recognizing the limitations and variability of these guidelines across different organizations. The study emphasizes the necessity for healthcare professionals to critically assess and apply guidelines based on the specific circumstances of each case, considering the best interest of the patient and involving them in the decision-making process. Additionally, it discusses the legal framework in Italy, particularly the evolution from the 2012 Balduzzi law to the 2017 Gelli-Bianco law, which seeks to provide greater clarity and protection for medical practitioners adhering to validated guidelines. The article underscores the ethical imperative for physicians to exercise their professional judgment and autonomy, even when it means deviating from established guidelines, to ensure that patient care is personalized and aligned with the patient's values and conception of a dignified life. The ultimate decision on ANH should be made by the patient, based on a thorough evaluation of the risk-benefit ratio through interdisciplinary consultation.